Operation time and clinical outcomes for open infrarenal abdominal aortic aneurysms to remain stable in the endovascular era - Gruber, M.; Sotir, A.; Klopf, J.; Lakowitsch, S.; Domenig, C.; Wanhainen, A.; Neumayer, C.; Busch, A.; Eilenberg, W. (Frontiers in Cardiovascular Medicine, 2023)
Objective Endovascular aortic repair (EVAR) has become a routine procedure worldwide. Ultimately, the increasing number of EVAR cases entails changing conditions for open surgical repair (OSR) regarding patient selection, complexity, and surgical volume. This study aimed to assess the time trends of open abdominal aortic aneurysm (AAA) repair in a high-volume single center in Austria over a period of 20 years, focusing on the operation time and clinical outcomes. Materials and methods A retrospective analysis of all patients treated for infrarenal AAAs with OSR or EVAR between January 2000 and December 2019 was performed. Infrarenal AAA was defined as the presence of a >10-mm aortic neck. Cases with ruptured or juxtarenal AAAs were excluded from the analysis. Two cohorts of patients treated with OSR at different time periods, namely, 2000–2009 and 2010–2019, were assessed regarding demographical and procedure details and clinical outcomes. The time periods were defined based on the increasing single-center trend toward the EVAR approach from 2010 onward. Results A total of 743 OSR and 766 EVAR procedures were performed. Of OSR cases, 589 were infrarenal AAAs. Over time, the EVAR to OSR ratio was stable at around 50:50 (p = 0.488). After 2010, history of coronary arterial bypass (13.4% vs. 7.2%, p = 0.027), coronary artery disease (38.1% vs. 25.1%, p = 0.004), peripheral vascular disease (35.1% vs. 21.3%, p = 0.001), and smoking (61.6% vs. 34.3%, p < 0.001) decreased significantly. Age decreased from 68 to 66 years (p = 0.023). The operation time for OSR remained stable (215 vs. 225 min, first vs. second time period, respectively, p = 0.354). The intraoperative (5.8% vs. 7.2%, p = 0.502) and postoperative (18.3% vs. 20.8%, p = 0.479) complication rates also remained stable. The 30-day mortality rate did not change over both time periods (3.0% vs. 2.4%, p = 0.666). Conclusion Balanced EVAR to OSR ratio, similar complexity of cases, and volume over the two decades in OSR showed stable OSR time without compromise in clinical outcomes.